O princípio da presunção de inocência e a possibilidade de execução provisória da pena na jurisprudência do Supremo Tribunal Federal: analise do Habeas Corpus Nº 126.292/SP - Silva, Anna Karolina Paiva e (Universidade Federal Rural do Semi-Árido, 2017)
The purpose of this research is to analyze the legal possibility of the sentence provisional execution, after confirmation of the conviction by a decision pronounced by a collegiate body, even though the judgment appeals of an extraordinary nature (strictu sensu) and special . In order to do so, a study was first carried out on the definition of this constitutional principle, taking into account its fundamental bases, from the perspective of the two models defined by the Italian jurist Luigi Ferrajoli, the Guarani or cognitive system and the Antigarantist. Then, an analysis was made on the historical construction of the jurisprudence of the Brazilian Federal Supreme Court (STF) on the principle of comprehensiveness, presumption and innocence, based on the ministers arguments on their votes of some outstanding judges on the subject. Subsequently, it was discussed on the Court's change of understanding on the possibility of early execution of the sentence in the judgment of HC 126.292 / SP, mainly analyzing the points of controversy that were used in the ministers' arguments. Finally, in our conclusion, we present a synthesis results of this research, analyzing the principle understanding of thepresumption and innocence adopted by our Magna Carta and an evaluation of the (in) compatibility of the decision adopted by the STF in HC 126.292 / SP With the 1988 Constitution. The methodology used was eminently the bibliographical research, as theoretical works about the subject, procedural pieces and informative jurisprudential of the superior courts.
Artigo Acadêmico
Keywords: Princípio da presunção de inocência; Garantismo; Execução provisória da pena; Jurisprudência do Supremo Tribunal Federal HC 126.292/SP; HC 126.292/SP; Principle of Innocence presumption; Civil Rights Protection; Provisional Execution of Sentence; Jurisprudence of the Federal Supreme Court; HC 126.292 / SP; CIENCIAS SOCIAIS APLICADAS::DIREITO